Kontribusi Organizational Justice terhadap Employee Engagement pada Karyawan Gen Z di Jaringan Habepro Radionet Indonesia - Gita Syawla Indah Fitri; Zulian Fikry (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Maintaining employee engagement presents a significant challenge for organizations, particularly when dealing with Generation Z, who possess unique characteristics, strong technological orientation, and high expectations regarding fairness in the workplace. One crucial factor believed to influence the level of employee engagement is organizational justice. This concept encompasses employees’ perceptions of fairness in the distribution of outcomes (distributive justice), the procedures applied (procedural justice), interpersonal treatment (interpersonal justice), and the clarity of information provided (informational justice). This study aims to examine the contribution of organizational justice to employee engagement among Gen Z employees at the Habepro Radionet Indonesia network. The research employed a quantitative approach with a simple linear regression method. The study population comprised all permanent Gen Z employees working within the network, with a sample size of 35 respondents. Data were collected using an organizational justice questionnaire covering its four dimensions and the Employee Engagement Scale (EES) to measure engagement levels. Data analysis was conducted using SPSS software through a simple linear regression test. The results revealed that organizational justice has a significant effect on employee engagement (p < 0.05), with a coefficient of determination of 0.528. This indicates that 52.8% of the variation in employee engagement can be explained by perceptions of organizational justice, while the remaining percentage is influenced by other factors beyond the scope of this study. These findings highlight the strategic importance of implementing fairness principles within organizations to enhance employee engagement, especially among Gen Z employees who tend to be more sensitive to equitable treatment, transparency of information, and open communication. Therefore, organizations are encouraged to design policies, procedures, and workplace interactions that foster a sense of justice, thereby sustaining employee engagement and contributing positively to overall organizational performance.